Application of Crowdsourcing Technology In Terms Of Digitization of Supply Chain Strategy - E. Bronnikova; O. Kuljamina; M. Vinogradova (International Journal of Supply Chain Management, 2020)
Abstract— The article presents the study on the problem of crowdsourcing application in terms of digital development of supply chain strategy. The purpose of this study is to develop the algorithm of application of crowdsourcing technology in terms of digitalization of supply chain strategy in socio-economic processes. The application of crowdsourcing technology facilitates the search for the most effective solutions to enterprise’s problems, minimizing the time-related and financial costs for their development. In the framework of this study, the methods of analysis, comparative analysis, generalization, decomposition were used. The novelty of the research is in the detailed examination of the crowdsourcing technology, comprehensive description of the algorithm of its functioning with application in addressing various tasks of supply chain strategy. The findings of the study can help enterprises to elaborate the workflow supply chain management with regard to public opinion.